2020
DOI: 10.1021/acs.biomac.0c00264
|View full text |Cite
|
Sign up to set email alerts
|

Optical Control of Cytokine Signaling via Bioinspired, Polymer-Induced Latency

Abstract: Characterization of linker cleavage, conjugation schematic, spectral properties of light sources and linker compounds, and latent IL-15 activity photomodulation (PDF)

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 84 publications
1
22
0
Order By: Relevance
“…IL-2, IL-12, IL-15) can be blunted via conjugation with a photolabile polyethylene glycol (PEG) and recovered via brief, in this case blue, LED light exposure. 18 While these studies demonstrated the feasibility of in vivo cytokine photoactivation using tissue phantoms, we concluded that the clinical applications of this approach were limited to cutaneous or subdermal tissues and those accessible by in situ light sources (e.g. catheter-guided fiber lasers) as a result of efficient absorption and scattering of light by tissues and biological fluids at visible wavelengths.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…IL-2, IL-12, IL-15) can be blunted via conjugation with a photolabile polyethylene glycol (PEG) and recovered via brief, in this case blue, LED light exposure. 18 While these studies demonstrated the feasibility of in vivo cytokine photoactivation using tissue phantoms, we concluded that the clinical applications of this approach were limited to cutaneous or subdermal tissues and those accessible by in situ light sources (e.g. catheter-guided fiber lasers) as a result of efficient absorption and scattering of light by tissues and biological fluids at visible wavelengths.…”
Section: Introductionmentioning
confidence: 91%
“…Leveraging the ability of NIR photons to efficiently penetrate human tissues, here we advance our prior approach 18 to reversibly photocage immunostimulatory cytokines by using photo-labile PEG that de-shields in response to NIR rather than visible light. We show that LED light exposure of NIR-photocaged cytokines can be used to reversibly modulate cognate cytokine receptor signaling and enhance the activity of bispecific cancer immunotherapies that rely on T celldependent cytolysis.…”
Section: Introductionmentioning
confidence: 99%
“…b) Adapted with permission. [ 29 ] Copyright 2020, American Chemical Society. c) Adapted with permission.…”
Section: Immunostimulatory Cytokinesmentioning
confidence: 99%
“…Inspired by the ability of a subset of cytokines (e.g., TGF‐ β 1, IL‐1 α , IL‐33) to activate in response to various biological stimuli, [ 28 ] we recently hypothesized that modification of cytokines with photolabile polymers could blunt cytokine activity when conjugated, then restore protein function upon exposure to light, allowing for enhanced control over the location, strength, and timescale of cytokine signals (i.e., “photokines,” Figure 1b, Figure ). [ 29 ] We modified IL‐2, IL‐15, and IL‐12 with PEG (5–20 kDa) appended to various o ‐nitrobenzyl linkers and found that simple blue LED light exposure could selectively restore protein activity upon light exposure. Photolabile polymer modification, alone, favorably biased IL‐2 binding toward IL‐2R βγ c , much like NKTR‐214, and improved IL‐12 plasma half‐life 16‐fold following intravenous injection in C57BL/6 mice.…”
Section: Immunostimulatory Cytokinesmentioning
confidence: 99%
“…SMANCS neocarzinostatin chemotherapy and Movanik naloxone laxative) and 3) nucleic acids (e.g. Macugen anti-VEGF aptamer antiangiogenic) ( Perdue et al, 2020 ). More recently, polymer conjugation has demonstrated further clinical utility in stabilizing lipid nanoparticles used to deliver small interfering RNA (siRNA, Onpattro) for the treatment of hereditary transthyretin-mediated (hATTR) amyloidosis ( Zhang et al, 2020 ), as well as both current mRNA-based vaccines for SARS-CoV-2 (COVID-19), BNT162b2/Comirnaty and mRNA-1273/Spikevax ( Schoenmaker et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%